Multiple sclerosis: Neuroimmune crosstalk and therapeutic targeting - Charabati, Marc; Wheeler, Michael A; Weiner, Howard L; Quintana, Francisco J (Cell, 2023)
Multiple sclerosis (MS) is a chronic inflammatory and degenerative disease of the central nervous system afflicting nearly three million individuals worldwide. Neuroimmune interactions between glial, neural, and immune cells play important roles in MS pathology and offer potential targets for therapeutic intervention. Here, we review underlying risk factors, mechanisms of MS pathogenesis, available disease modifying therapies, and examine the value of emerging technologies, which may address unmet clinical needs and identify novel therapeutic targets.